OPTIMALIZING THE USE OF GO READING DIGITAL LIBRARY IN INCREASING STUDENT'S READING INTEREST IN ONLINE LEARNING - Tustiana Windiyani; Yuli Mulyawati; Putri Nabil; Diani Ranti (PrimaryEdu : Journal of Primary Education, 2022)
During the current covid-19 pandemic, students are required to be more independent in learning, especially increasing interest in reading because reading is a gateway to find information. This study aims to increase interest in reading through a digital library application called Go Reading. With Go Reading Students can easily access reading anytime and anywhere, without having to bother carrying piles of books. The research method used is Research and Development. Research and Development was modified by researchers only up to 6 steps. Based on the results of interviews and the distribution of response questionnaires to the use of the Go Reading digital library application to increase reading interest, the results with high criteria indicate that the use of the application can be categorized as optimally increasing students' reading interest. The conclusion is that in optimizing digital libraries, students must be actively involved in increasing their learning independence, and there is awareness in students and the role of parents and teachers in directing, supervising, guiding, and motivating students in optimizing the role of digital libraries in online learning.